Use of wound dressings to enhance prevention of pressure ulcers caused by medical devices. Issue 3 (1st July 2013) - Black, Joyce; Alves, Paulo; Brindle, Christopher Tod; Dealey, Carol; Santamaria, Nick; Call, Evan; Clark, Michael
Abstract Medical device related pressure ulcers (MDR PUs) are defined as pressure injuries associated with the use of devices applied for diagnostic or therapeutic purposes wherein the PU that develops has the same configuration as the device. Many institutions have reduced the incidence of traditional PUs (sacral, buttock and heel) and therefore the significance of MDR PU has become more apparent. The highest risk of MDR PU has been reported to be patients with impaired sensory perception, such as neuropathy, and an impaired ability for the patient to communicate discomfort, for example, oral intubation, language barriers, unconsciousness or non‐verbal state. Patients in critical care units typify the high‐risk patient and they often require more devices for monitoring and therapeutic purposes. An expert panel met to review the evidence on the prevention of MDR PUs and arrived at these conclusions: (i) consider applying dressings that demonstrate pressure redistribution and absorb moisture from body areas in contact with medical devices, tubing and fixators, (ii) in addition to dressings applied beneath medical devices, continue to lift and/or move the medical device to examine the skin beneath it and reposition for pressure relief and (iii) when simple repositioning does not relieve pressure, it is important not to create more pressure by placing dressings beneath tight devices.